FORMULASI SEDIAAN MASKER CLAY DARI EKSTRAK DAUN PIDADA MERAH (Sonneratia caseolaris) SEBAGAI ANTIOKSIDAN - Eka Kumalasari; Regita Ayu Wulandari; Noor Aisyah; Dwi Rizki Febrianti; Rakhmadhan Niah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
One of the causes of skin damage is free radicals, to counteract free radicals it can be inhibited using antioxidants. The use of natural antioxidants is considered safer because they are obtained from plant extracts. Red pidada leaf extract has a very strong antioxidant activity with an IC₅₀ value of 24.22 ppm. This plant contains compounds of alkaloids, flavonoids, tannins, saponins, and phenols. This study aims to determine the results of the physical properties test and then determine the formula that better meets the requirements of a good clay mask. The preparation of red pidada leaf extract was carried out using the maceration method with 96% ethanol as solvent. In formula 1 and formula 2 there are variations in the concentration of kaolin clay base and bentonite. The tests carried out were physical properties test of the preparation which included organoleptic test, homogeneity test, pH test, dispersion test, and dry time test . The results showed that all clay mask formulations were declared to meet the physical properties test requirements. In formula 2, the clay mask preparation is a better formulation than formula 1, because in formula 2 it produces greater dispersion, and the dry time is faster.